Light microscopy and surface topography of Urotrema scabridum and Renschetrema indicum (Digenea) from Rhinopoma hardwickii (Chiroptera): first report in Egypt - Kareem Morsy (Revista Brasileira de Parasitologia Veterinária, 2018)
Abstract This report introduced the description of two different species of digenean parasites isolated from the intestine of Rhinopoma hardwickii with new host and locality records in Egypt. The recovered helminthes were studied morphologically and morphometrically by light microscopy and the surface topography of the two species was elucidated by scanning electron microscopy (SEM). Urotrema scabridum had an elongated body, testes were tandem, ovaries were pretesticular, and vitelline follicles were observed in 2 lateral fields. SEM showed that the anterior half was covered with random and backwardly directed tegument spines. The lumen of the oral sucker was as a longitudinal slit encircled with type I dome-shaped papillae. The ventral sucker was wrinkled and covered by tongue-shaped tegument spines and several scattered papillae. Renschetrema indicum had a fusiform body with minute spines densely distributed in the anterior part of the body; testes sub-triangular, ovary fusiform; vitellaria were randomly distributed around the ceca and genital organs. SEM showed that the fore-body was ventrally concave and surrounded by cytoplasmic ridges equipped with numerous closely packed claw-shaped spines. The oral sucker was externally surrounded by two circles of papillae while the lip of the ventral sucker was rounded and surrounded by three papillae located in its upper end and anterolaterally.